Chrześcijaństwo w kulturze amerykańskiej - Perszon, Jan (Studia Nauk Teologicznych PAN, 2010)
This paper constitutes out of necessity only a partial/fragmentary analysis of the influence of Christianity on the culture of the United Sates. There is no doubt that the wish to create a truly Christian society which could be a “new Israel” was a strong motive which became the underlying cause for the founding of the USA. The “founding myth” has been reflected not only in the proclaimed constitution with a pioneering principle of separating the state from the religion but also present in everyday life of a rapidly developing nation, continually fuelled by Protestant leaders. The power of the myth was sustained and spontaneously stimulated by the successive waves of European immigrants systematically Americanized by the local population. The inseparable element of American lifestyle is a specific presence of Christianity in the public sphere in the form of civil religion. After the crisis associated with the expansion of secularism (intellectuals’ heresy after the Second World War) there was a great revival of Christianity in the eighties of the previous century. It was influenced by a fervent religious rhetoric of President R. Reagan and by the attack of Protestant conservatives soon allied with conservatism of Catholic writers/publicists. Despite the growing attitudes of religious indifference, political and social life of contemporary America is permeated with religious elements, declaration of faith in God being perceived positively. A marked religious revival although encompassing only some part of the society makes America, in contrast to Europe, a country of a clearly Christian character.